Campylobacter jejuni in poultry production and processing in relation to public health - Abdul Aziz, Saleha; Mead, G. C.; Ibrahim, A. L. (World's Poultry Science Association, 1998)
In recent years it has been shown that Campylobacter jejuni is the most common cause of gastroenteritis or enterocolitis in man, especially in developed countries. Numerous studies have demonstrated a high prevalence of C. jejuni in chickens and it is evident that chicken meat is a significant source of human gastroenteritis due to lack of care in handling raw products and inadequate cooking. Campylobacter spp. are frequently found in the intestinal tract of poultry where colonization leads to contamination of carcasses during processing, especially at the defeathering and evisceration stages. This paper reviews the occurrence of C. jejuni in poultry, particularly in the live bird and on processed carcasses. It also considers possible factors in the introduction and spread of C. jejuni on farms and discusses progress in developing measures for controlling Campylobacter spp. in the production chain.